Longitudinal Changes in the Eating Habits of Patients with Cancer Receiving Palliative Care - Nagihan Yıldız ÇELTEK; Ufuk ÜNLÜ; Rıza ÇITIL; Yalçın ÖNDER; Mustafa SÜREN; İsmail OKAN (Bezmiâlem Science, 2021)

(untitled)
Objective:Nutritional changes are frequently observed in patients with cancer because of multiple symptoms. This study aimed to determine food types most preferred by the patients and most suitable to them and to identify methods to enrich these food options in the future.Methods:This cross-sectional, descriptive study was conducted on 151 patients at Tokat Gaziosmanpaşa University Palliative Care Center. Demographic data, nutritional habits, and food preferences were obtained using a questionnaire. The Karnofsky performance scale (KPS) was also used.Results:Of the 151 patients, 53.6% (n=81) were male, and the mean patient age was 62.7±14.7 years. Moreover, 47% (n=71) of the patients were bothered by the food odor; specifically, 27.8% reported that the food had a disturbing smell. The average KPS score was 63.9±15.0 points. The mean KPS scores were significantly higher in the eating group (p=0.043). Patients most preferred yayla (39.7%) among soups and yogurt (28.8%) among milk products. Only 36.4% (n=55) of the patients stated that they could continue to use enteral nutrition products at the recommended dosage regularly, but 38% (n=21) have been consuming enteral nutrition products.Conclusion:When offering healthy food options, patients should have sufficient calorie intake and consume foods that they think are delicious. Starting enteral nutrition products early is recommended to avoid malnutrition.